THE EFFECT OF ENTREPRENEURIAL ORIENTATION, MOTIVATION, AND DIGITAL TECHNOLOGY ON THE PERFORMANCE OF VILLAGE-OWNED ENTERPRISES WITH INNOVATION AS A MODERATING VARIABLE - Raihan Rizqy Arrasyid; Rizal Yaya (Mega Aktiva, 2025)
This study seeks to provide empirical evidence on the effects of entrepreneurial orientation, motivation, and digital technology on the performance of Village-Owned Enterprises (BUMDes), with innovation examined as a moderating variable. The research focuses on BUMDes located in Gunungkidul Regency, with participants consisting of BUMDes managers, including directors, secretaries, treasurers, and heads of business units. A quantitative approach was employed, utilizing primary data collected through structured questionnaires. The sample comprised 55 BUMDes selected through purposive sampling. Data analysis was conducted using SmartPLS 4.0 and IBM SPSS version 22. The findings reveal that both entrepreneurial orientation and motivation have a positive impact on BUMDes performance. However, digital technology does not significantly influence performance, and innovation does not moderate the relationship between entrepreneurial orientation and BUMDes performance.